Cyclophilin B as a co-regulator of prolactin-induced gene expression and function in breast cancer cells - Fang, Feng (2010)
The effects of prolactin (PRL) during the pathogenesis of breast cancer are mediated in part though Stat5 activity enhanced by its interaction with its transcriptional inducer, the prolyl isomerase cyclophilin B (CypB). We have demonstrated that knockdown of CypB decreases cell growth, proliferation, and migration, and CypB expression is associated with malignant progression of breast cancer. In this study, we examined the effect of CypB knockdown on PRL signaling in breast cancer cells. CypB knockdown with two independent siRNAs was shown to impair PRL-induced reporter expression in breast cancer cell line. cDNA microarray analysis was performed on these cells to assess the effect of CypB reduction, and revealed a significant decrease in PRL-induced endogenous gene expression in two breast cancer cell lines. Parallel functional assays revealed corresponding alterations of both anchorage-independent cell growth and cell motility of breast cancer cells. Our results demonstrate that CypB expression levels significantly modulate PRL-induced function in breast cancer cells ultimately resulting in enhanced levels of PRL-responsive gene expression, cell growth, and migration. Given the increasingly appreciated role of PRL in the pathogenesis of breast cancer, the actions of CypB detailed here are of biological significance.